2015
DOI: 10.1002/2015ja021211
|View full text |Cite
|
Sign up to set email alerts
|

Statistical characterization of the foremoon particle and wave morphology: ARTEMIS observations

Abstract: Although the zeroth‐order picture of the Moon‐solar wind interaction involves no upstream perturbation, the presence of the Moon does affect the upstream plasma in a variety of ways. In this paper, a large volume of data obtained by the dual‐probe Acceleration, Reconnection, Turbulence and Electrodynamics of the Moon's Interaction with the Sun (ARTEMIS) mission are used to characterize the large‐scale morphology of the “foremoon,” which is defined as the region upstream of the Moon and its wake that contains M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 63 publications
(116 reference statements)
5
61
0
Order By: Relevance
“…A further analysis revealed that the total power enhancement is connected also with the enhanced compressibility from a value of 0.03 that is typical for SW fluctuations (Šafránková et al, 2019) to about >0.2 in the region of the maximum deceleration ( Figure 5). Moreover, we have found a similar enhancement of the compressibility near the Moon and attributed it to an excitation of compressive waves as a result of the interaction of the incoming SW with particles reflected from the lunar surface (Harada et al, 2015). A careful examination of Figure 4b shows a slightly decreased proton speed in a similar area of the D − Θ BN space with respect to the surrounding bins.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…A further analysis revealed that the total power enhancement is connected also with the enhanced compressibility from a value of 0.03 that is typical for SW fluctuations (Šafránková et al, 2019) to about >0.2 in the region of the maximum deceleration ( Figure 5). Moreover, we have found a similar enhancement of the compressibility near the Moon and attributed it to an excitation of compressive waves as a result of the interaction of the incoming SW with particles reflected from the lunar surface (Harada et al, 2015). A careful examination of Figure 4b shows a slightly decreased proton speed in a similar area of the D − Θ BN space with respect to the surrounding bins.…”
Section: Discussionsupporting
confidence: 58%
“…A typical value of the compressibility of the SW fluctuations is about 0.03 and does not depend on the frequency through the inertial range (Šafránková et al, 2019). We assume that the enhanced compressibility can be caused by the modification of the SW wave field by a presence of ions reflected from the lunar surface (Harada et al, 2015;Lue et al, 2018). Surprisingly, a larger portion of compressive fluctuations is observed at the lower frequency (0.005 Hz, left panels).…”
Section: Discussionmentioning
confidence: 93%
“…The separations of the ARTEMIS spacecraft from the Moon were 10.2 and 2.6 lunar radii (R L ) along the Sun-Moon line and 2.0 R L and 10.7 R L perpendicular to it for P1 and P2, respectively. According to Harada et al (2015) these distances are large enough so that no significant Moon-related ion fluxes Ion populations at an IP shock 7 should be detected by either of the ARTEMIS spacecraft. Also, the IMF orientation indicates that the spacecraft were not magnetically connected to the Moon nor to the Earth's bow-shock ( Figure 1).…”
Section: Datasetsmentioning
confidence: 99%
“…The crustal field reflects incident ions more effectively, generates the electric field originating from the difference of Larmour radii between the ions and electrons, and causes mirror reflections of incident electrons which results in field-aligned electron beams (Bhardwaj et al, 2015;Lue et al, 2011;Saito et al, 2010Saito et al, , 2012. The absorption and reflection by the Moon modifies the velocity distribution of the plasma around the Moon, to be an energy source of the wave activities (Halekas et al, 2006(Halekas et al, , 2013Harada & Halekas, 2016;Harada et al, 2015;Nakagawa, 2016;Nakagawa et al, 2011Nakagawa et al, , 2012.…”
Section: 1002/2017ja024505mentioning
confidence: 99%